Sympathectomy versus Sympathicotomy in Palmar Hyperhidrosis Comparing T3 Ablation - Aydemir, Bülent; Imamoglu, Oya; Okay, Tamer; Celik, Muharrem (The Thoracic and Cardiovascular Surgeon, 2015)
Objective The objective of this study was to evaluate and compare thoracoscopic sympathectomy and sympathicotomy at the third ganglia (T3) level for the treatment of primary palmar hyperhidrosis in terms of initial surgery results, complications, and patient satisfaction.Materials and Methods Two groups of patient underwent T3 thoracoscopic sympathectomy and thoracoscopic sympathicotomy under general anesthesia using single-lung ventilation via a double-lumen endotracheal tube by the same surgical team for the treatment of severe primary palmar hyperhidrosis or a combination of levels for multiarea between 2008 and 2013. The groups were homogeneous for relevant demographic, physiological, and clinical data. All patients were examined preoperatively and were followed up at 6 months postoperatively. In both groups, patient's satisfaction was evaluated 6 months after surgery by a detailed interview and scored into three grades (1 = very satisfied, 2 = satisfied, and 3 = dissatisfied).Results No operative mortality, major intraoperative complication, infections, and Horner syndrome were recorded. There was no treatment failure. The average time of operation was 50 minutes for Group A (sympathectomy) and 36 minutes for Group B (sympathicotomy). Compensatory sweating occurred in 40 patients (89% for Group A and 85.11% for Group B) with a different accumulation of the severity degree. The satisfaction rate was 91.11% for Group A and 93.61% for Group B.Conclusion There was no significant difference between thoracoscopic sympathectomy and sympathicotomy at the third ganglia (T3) level for the treatment of primary palmar hyperhidrosis in terms of initial surgery results, complications, and patient satisfaction. Neither surgical technique is better than the other one for palmar hyperhidrosis treatment. Development of severe compensatory sweating and postoperative pain are major determinant factors of patient dissatisfaction. Sympathicotomy should be preferred for palmar hyperhidrosis treatment, as it is much technically shorter, simpler to implement, and also easier to learn.
Keywords: hyperhidrosis; sympathectomy; compensatory sweating